The Influence of the Transition from Primary to Secondary Schooling in the Motivation for Learning English of Seventh Grade Students at Institución Educativa Rafael Uribe Uribe (2016)
This study aimed at investigating the influence of the transition from primary to secondary schooling in the motivation for learning English and the possible factors that influence the motivation, positively or negatively, of the students in seventh grade. This research was carried out at Institución Educativa Rafael Uribe Uribe. The subjects to be studied in the research were two groups: students from fifth grade and students from seventh grade. The study comprises the qualitative data. The data were collected by applying the next set of instruments: class’s observations, two focal groups, one from each grade; interviews with both teachers, and surveys for three randomly selected parents from each students from each grade. The findings of this study indicated that motivation for learning English is, in general terms, negatively influenced by the transition from primary to secondary school due to the type of motivation developed, academic changes and the modification of social needs.